2016
DOI: 10.14814/phy2.12739
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hemorrhage rate on early hemodynamic responses in conscious sheep

Abstract: Physiological compensatory mechanisms can mask the extent of hemorrhage in conscious mammals, which can be further complicated by individual tolerance and variations in hemorrhage onset and duration. We assessed the effect of hemorrhage rate on tolerance and early physiologic responses to hemorrhage in conscious sheep. Eight Merino ewes (37.4 ± 1.1 kg) were subjected to fast (1.25 mL/kg/min) and slow (0.25 mL/kg/min) hemorrhages separated by at least 3 days. Blood was withdrawn until a drop in mean arterial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…To demonstrate the proposed framework we compare two configurations of a warning index applied to predict a hemorrhage-induced drop in blood pressure in conscious sheep from a previously reported study [20]. Experiments were performed at the University of Texas Medical Branch under a protocol reviewed and approved by the Institutional Animal Care and Use Committee and conducted in compliance with the guidelines of the National Institutes of Health and the American Physiological Society for the care and use of laboratory animals.…”
Section: Experimental Methods For Case Examplementioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the proposed framework we compare two configurations of a warning index applied to predict a hemorrhage-induced drop in blood pressure in conscious sheep from a previously reported study [20]. Experiments were performed at the University of Texas Medical Branch under a protocol reviewed and approved by the Institutional Animal Care and Use Committee and conducted in compliance with the guidelines of the National Institutes of Health and the American Physiological Society for the care and use of laboratory animals.…”
Section: Experimental Methods For Case Examplementioning
confidence: 99%
“…t event was defined by the stopping point of hemorrhage in the previously reported study as the time mean arterial pressure decreased during hemorrhage 30 mmHg mean arterial pressure from baseline [20]. For this demonstration, we defined T min and T max as 1 and 14 min before t event , respectively.…”
Section: Experimental Methods For Case Examplementioning
confidence: 99%
“…The compensatory mechanisms to hypovolemia include an early sympathetic response characterized by increased heart rate and systemic increments in vascular resistance, which are mostly mediated by the action of catecholamines, especially noradrenaline, in cardiac muscle and in arteriolar smooth muscle cells. 27,28 In addition, this compensatory vasoconstriction is mediated by thromboxane A2-triggered signaling in smooth muscle cells. 29 It has been demonstrated that plasma levels of thromboxane A2 are significantly lower in dengue shock syndrome patients than in healthy populations and patients with dengue hemorrhagic fever but without shock.…”
Section: Discussionmentioning
confidence: 99%
“…Following the post-transfusion period (after data recording ended) on the first day of experiment the remaining blood was reinfused. Three (or more) days later, the experiment was repeated on each animal at the alternate hemorrhage rate of the first day [1] .
Fig.
…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The data set comprises experimental information (e.g., hemorrhage rate, animal weight, event times), physiological waveforms (arterial and central venous blood pressure, electrocardiogram), time-series records of non-invasive physiological measurements (SpO 2 , tissue oximetry), intermittent arterial and venous blood gas analyses (e.g., hemoglobin, lactate, SaO 2 , SvO 2 ) and intermittent thermodilution cardiac output measurements. A detailed explanation of the hemodynamic and pulmonary changes during hemorrhage is available in a previous publication (Scully et al, 2016) [1] .…”
mentioning
confidence: 99%